Gender and physical education : contemporary issues and future directions - Penney, Dawn. (London : Routledge, 2002)
The book challenges our understandings of gender, equity and identity in PE, establishing a conceptual and historical foundation for the issue, as well as presenting a wealth of original research material.
Includes bibliographical references and index.
Keywords: Physical education and training -- social aspects; Sexism in education; Gender identity in education